Analisis Risiko Keamanan Siber dalam Transformasi Digital Pelayanan Publik di Indonesia - Alfi, Muhammad; Yundari, Ni Putu; Tsaqif, Ahnaf (UI Scholars Hub, 2023)
The Industrial Revolution 4.0 has now brought many changes in its development where public services are increasingly integrated with information technology. In responding to global developments, the Indonesian government is carrying out an adaptation process by transforming public services in order to improve the quality and equality of public services.. However, cyber security risks are a serious challenge that can hinder sustainability and success in transformation. Through a comprehensive literature review, this research describes the development of digital transformation in Indonesia, applicable cybersecurity policies and regulations, as well as relevant risk analysis methodologies. The research findings show that strong policies and increased public awareness are important to protect the digital infrastructure of public services. Identification of potential threats, system vulnerabilities, and related attack case studies provide the basis for formulating effective risk mitigation strategies. This research provides a comprehensive view of the challenges and opportunities in dealing with cyber security risks, as well as providing reflections as a form of effort to make policy recommendations that can strengthen cyber security protection and increase the resilience of public services in the era of digital transformation